Survai Tingkat Perkembangan Kemampuan Motorik Siswa Sekolah Menengah Pertama di Kecamatan Todanan Kabupaten Blora (Universitas Negeri Semarang, 2021)
The development of motor ability plays an important and influential role in the development and growth of each individual's mobility skills. Based on obervasi results, students do very little movement and physical activity one that makes students move a little bit, namely gadgets. The problem of research is: